OP0222 TSLP expression is increased in RA joints and causes increased activation of intra-articular myeloid dendritic cells with enhanced stimulation of TH1 and TH17 activity. (23rd January 2014) - Moret, F.M.; van der Wurff-Jacobs, K.M.; Hack, C.E.; Lafeber, F.P.; van Roon, J.A.
Abstract : Background: Thymic stromal lymphopoietin (TSLP) is well known for its potent activation of myeloid dendritic cells (mDCs) resulting in Th2-mediated immune responses. TSLP signals cells via the IL-7 receptor-alpha chain (IL-7Rα), shared with IL-7, together with the TSLP receptor (TSLPR) subunit. Recently, we have demonstrated that prevention of TSLPR signalling strongly reduces Th17-driven experimental arthritis and immunopathology. Furthermore, we have shown that administration of TSLP enhances severity of inflammation and joint destruction in collagen induced arthritis. Objectives: To determine the levels of TSLP and numbers of TSLPR-expressing mDCs in joints of rheumatoid arthritis (RA) patients as compared to peripheral blood (PB) and the capacity of TSLP to induce mDC-dependent T-cell activation. Methods: TSLP was measured in synovial fluid (SF) of patients with RA (n=50) and osteoarthritis (OA, n=24) by ELISA. CD1c+ mDC numbers and TSLPR expression on these cells were assessed by FACS analysis in paired samples of SF and PB from RA patients (n=9). CD1c+ mDCs, isolated from PB as well as SF of RA patients (n=6), were stimulated with TSLP for 20 hours and cytokine production was measured by multiplex immunoassay (measuring 51 cytokines). Washed TSLP-activated CD1c+ mDCs from PB (n=11) and SF (n=5) were added to autologous CD4 T cells in the absence of additional stimuli, cultured for 6 days and subsequently proliferation was measured. Additionally, T-cell cytokine production was measured (by ELISA) upon restimulation with ionomycin/PMA. Results: TSLP levels in SF of RA patients were significantly increased compared to OA patients (mean 297 vs. 80 pg/ml, resp., p<0.01). mDCs numbers from SF were significantly increased compared to PB (5.0% vs. 0.6%, resp., p<0.01) and expressed increased levels of TSLPR (MFI 24 vs. 15, resp., p<0.01). TSLP significantly stimulated production of chemokines TARC and MIP1α by mDCs from PB and SF (TARC: PB from 1 to 42 pg/ml, p<0.05 and SF from 26 to 186 pg/ml, p<0.05; MIP1α: PB from 1268 to 5486 pg/ml, p<0.05 and SF from 2776 to 3733 pg/ml, p<0.05). Upon incubation with TSLP, TSLPR-expressing mDCs from PB potently stimulated proliferation of autologous CD4 T cells as compared to unstimulated mDCs (ratio T cell:DC 5:1, from 1503 to 16036 cpm, p<0.01). However, TSLP-mDCs from SF had a strongly increased capacity to activate CD4 T cells (ratio T cell:DC 5:1, from 26395 to 57387 cpm, p<0.05). Enhanced proliferation was associated with increased production of IFNγ (ratio T cell:DC 5:1, PB from 179 to 655 pg/ml, p<0.01 and SF from 601 to 1867 pg/ml, p<0.05), IL-17 (PB from 39 to 353 pg/ml, p<0.05 and SF from 363 to 1382 pg/ml, p<0.05), and IL-4 (PB from 17 to 246 pg/ml, p<0.01 and SF from 193 to 775 pg/ml, n.s.). Conclusions: Our data indicate that increased intra-articular TSLP concentrations in RA potently activate TSLPR-expressing mDCs from SF to secrete enhanced levels of proinflammatory mediators causing T cell chemotaxis and to potently increase arthritogenic T cell activation. This suggests that TSLP and TSLPR-expressing mDCs could both play an essential role in the immunopathology of RA. Disclosure of Interest: None Declared